Mass Spectrometry Imaging as a New Method: To Reveal the Pathogenesis and the Mechanism of Traditional Medicine in Cerebral Ischemia - Liang, Yan; Feng, Qiaoqiao; Wang, Zhang (Frontiers in Pharmacology, 2022)
Mass spectrometry imaging (MSI) can describe the spatial distribution of molecules in various complex biological samples, such as metabolites, lipids, peptides and proteins in a comprehensive way, and can provide highly relevant supplementary information when combined with other molecular imaging techniques and chromatography techniques, so it has been used more and more widely in biomedical research. The application of mass spectrometry imaging in neuroscience is developing. It is very advantageous and necessary to use MSI to study various pathophysiological processes involved in brain injury and functional recovery during cerebral ischemia. Therefore, this paper introduces the techniques of mass spectrometry, including the principle of mass spectrometry, the acquisition and preparation of imaging samples, the commonly used ionization techniques, and the optimization of the current applied methodology. Furthermore, the research on the mechanism of cerebral ischemia by mass spectrometry was reviewed, such as phosphatidylcholine involved, dopamine, spatial distribution and level changes of physiological substances such as ATP in the Krebs cycle; The characteristics of mass spectrometry imaging as one of the methods of metabolomics in screening biomarkers related to cerebral ischemia were analyzed the advantages of MSI in revealing drug distribution and the mechanism of traditional drugs were summarized, and the existing problems of MSI were also analyzed and relevant suggestions were put forward.